Ghost Soldiers : The Forgotten Epic Story of World War II's Greatest Rescue Mission - Sides, Hampton (New York Anchor Books, 2002)
The rescue of over 500 American POWs from a Japanese camp in the Philippines in 1945 was the largest and most successful operation of its kind. Based on personal accounts from the survivors, this is an epic story now told in full for the first time.
Include Maps
Keywords: World War (1939-1945) -- United States. Army. Ranger Battalion, 6th -- Philippines--Cabanatuan